Giant lipoleiomyoma of uterus mimicking ovarian dermoid cyst: a rare case report - Jain, Akanksha; Sinha, Navin Kumar; Khandelia, Binet (Annals of Pathology and Laboratory Medicine, 2015)
Lipomatous tumors of uterine origin are unusual benign neoplasms. The histological spectrum includes lipoleiomyoma, fibrolipomyoma,angiomyolipoma, pure lipomas and leiomyoliposarcoma depending open various compositions of mesodermal tissue. The tumor consists of long intersecting bundles of bland, smooth muscle cells admixed with nests of mature fat cells and fibrous tissue.They are typically found in postmenopausal women and are associated with ordinary leiomyomas. However, giant lipoleiomyomas more than 20 cm are rare and cause diagnostic dilemma on imaging studies as they need to be differentiated with ovarian dermoid cyst. We report this unusual case of uterine lipoleiomyoma because of its rarity and giant size.